Natural selection contributes to food web stability - Mougi, Akihiko (PLOS ONE, 2020)
How biodiversity is maintained in ecosystems is a central issue in ecology. According to the evolutionary theory, heritable variations between individuals are important for the generation of species diversity, linking both intra and interspecific variations. The present food web model shows that intraspecific variations via natural selection also play crucial roles in maintaining the stability of large communities with diverse species. In particular, our computations indicate that larger communities need more intraspecific variation to be maintained and are powerfully stabilized when multiple traits are variable. Consequently, these variations are likely to be maintained in larger communities. Hence, intra and interspecific diversities may support each other during evolution.